Logic: or, The morphology of knowledge - Bosanquet, Bernard (The Clarendon Press, 1911)
v. 1. Introduction -- Of judgment and judgment-forms in general -- Quality and comparison -- Quality and proportion -- Measurement (continued)/Abstract quantity -- Singular and universal judgment -- Universal judgment (continued) -- Negation, opposition, and conversion -- Disjunction and the statement of chances -- Modality -- v. 2. The nature of inference -- Enumerative induction and mathematical reasoning -- Analogy -- Scientific induction by perceptive analysis -- Scientific induction by hypothesis/Generalisation -- Concrete systemic inference -- The relation of knowledge to its postulates -- The above theory of judgment in relation to absolutism -- Truth and coherence -- The relation of mental states to judgment and to reality